O argumento judicial consequencialista na vis??o da an??lise econ??mica do direito e o desenvolvimento brasileiro - Correia, ??ngela Karine G. de Miranda (2015)
Access to the courts is Constitutionally expressed. The jurisdiction has to replace function parties for the decision. Judge, as a representative of State, has the task to substitute the desire of the parties to resolve the conflict safeguarding the legal system. Thus, should the magistrate, according to the Civil Law system, positivist in nature, draw on rules / rules contained in the legal system, which are public knowledge, to put it right and bring the parties and the company legal security It is sought. The objective of this work is to demonstrate that although linked to the Civil Law system, the Brazilian Judiciary, must employ a microeconomic concepts, through the Economic Analysis of Law, to identify the possible choices, limited by the standard, which can serve for the taking decisions that will influence national development, which in this work is called the consequentialism and pragmatism.